Electrical machines and drives systems - Hindmarsh, John (Newnes, an imprint of Elsevier Science, 1996)
Recent years have brought substantial developments in electrical drive technology, with the appearance of highly rated, very-high-speed power-electronic switches, combined with microcomputer control systems. This popular textbook has been thoroughly revised and updated in the light of these changes. It retains its successful formula of teaching through worked examples, which are put in context with concise explanations of theory, revision of equations and discussion of the engineering implications. Numerous problems are also provided, with answers supplied